Diabetes in Women Pathophysiology and Therapy - Tsatsoulis, Agathocles; Wyckoff, Jennifer; Brown, Florence M.; SpringerLink (Online service) (Totowa, NJ : Humana Press, 2010)
Gender differences impact the pathophysiology and clinical burden of diabetes in women. Exploring the complex interplay between gender and diabetes, Diabetes in Women provides a state-of-the-art update from conception to menopause and beyond. Written by experts in the field, Diabetes in Women covers sex differences in cardiometabolic risk, the impact of diabetes on women$1 (Bs health, diabetes and pregnancy, offspring of the diabetic mother and the disease management of women with diabetes. Chapters include up to date information on cardiometabolic risk in women throughout the lifecycle and the differences between sexes in energy balance and body composition. Prominent authors also explore the impact of poverty and globalization on the emerging epidemic of obesity in developing countries. Designed for primary care and internal medicine physicians, endocrinologists, obstetricians and gynecologists, and trainees and basic scientists in these areas, Diabetes in Women is an invaluable resource and important contribution to the field.s
Sex Differences in Energy Balance, Body Composition, and Body Fat Distribution -- Menopause and Diabetes Mellitus -- Cardiovascular Disease in Women with Diabetes -- Insulin Resistance, Diabetes, and Cardiovascular Risk in Women and the Paradigm of the Polycystic Ovary Syndrome -- Developmental Programming of Polycystic Ovary Syndrome: Role of Prenatal Androgen Excess -- An Anthropological View of the Impact of Poverty and Globalization on the Emerging Epidemic of Obesity -- Eating Disorders and Depression in Women with Diabetes -- Sexual Health in Women with Diabetes -- Contraception for Women with Diabetes -- The Effect of PCOS on Fertility and Pregnancy -- The Effect of Pregnancy on Energy Metabolism, Body Composition, and Endothelial Function -- The Epidemiology of Diabetes in Women and the Looming Epidemic of GDM in the Third World -- Gestational Diabetes Mellitus: Diagnosis, Maternal and Fetal Outcomes, and Management -- Nutrition and Pregnancy -- Preconception Care for Women with Diabetes Mellitus -- Obstetric Care of the Woman with Diabetes -- Medical Management of Preexisting Diabetes in Pregnancy -- Use of Ultrasound in the Metabolic Management of Gestational Diabetes and Preexisting Diabetes Mellitus in Pregnancy -- Preeclampsia -- The Infant of the Diabetic Mother: Metabolic Imprinting -- The Genetic Basis of Diabetes -- Breastfeeding and Diabetes -- Management of Disease in Women with Diabetes.
Keywords: Medicine; General practice (Medicine).; Gynecology; Obstetrics; Diabetes; Endocrinology; Medicine & Public Health; Diabetes; Endocrinology; General Practice / Family Medicine; Gynecology; Obstetrics/Perinatology.; Electronic books